PENGARUH MEDIA PEMBELAJARAN VISUAL TERHADAP MOTIVASI BELAJAR - Zahra, Rizkiana (2016)
Penelitianinibertujuanuntukmengetahuipengaruh media pembelajaran visual yaituberupaprezidanflash cardterhadapmotivasibelajar. Objekpadapenelitianiniadalahpesertadidikkelas XII IPS di SMA Al-Ma'soem. Metodepenelitian yang digunakanadalahmetode quasi eksperimen.Desainpenelitianiniadalahone group pretest posttest design. Adapunteknikpengumpulan data yang digunakanadalahpemberiankuisionertentangmotivasibelajarkepadapesertadidik di kelas XII IPS di SMA Al-Ma'soemsaatsebelumdansesudahpembelajaranmenggunakan media pembelajaran visual. Teknikanalisis data menggunakanujiwilcoxondengantarafsignifikan 5%. Sebelumdilakukananalisis data, terlebihdahuludilakukanujiprasyaratanalisisberupaujinormalitasdanujihomogenitas. Pengujiandilakukandenganbantuan program SPSS 16.0 menunjukan data pretestdanposttesttidakberdistribusi normal dantidakhomogen. BerdasarkanujiwilcoxonpadakolomAsymp. Siglebihkecildaritarafsignifikansi 5% (0.000<0,005). Hasilpenelitianinimenunjukanadanyaperbedaanmotivasibelajarantarasebelumdansesudahmenggunakan media pembelajaran visual;-- This study aims todetermine the influences of visual learning media in the form of prezi and flash card towards learning motivation.The object of this study is students of grade XII Social Science Education in Al-Ma'soem High School.The method used in this study is a quasi-experimental method. Furthermore, the research design applied is a one group pretest posttest design. For data collection, questionnaires about learning motivation were given to students in grade XII Social Science Education of Al-Ma'soem High School, before and after learning session with a visual learning media. The data were analyzed by using wilcoxon test technique with significant grade level of 5%. Prior to the data analysis, it was firstlytested with prerequisite test analysis in the form of normality and homogeneity test. The tests, performed with SPSS 16.0 program, shows that pretest and posttest data are not distributed normally and homogeneously. Based on wilcoxon test of Asymp column, sig is smaller than significance grade level of 5% (0,000<0,005).Thus, the result of this study reveals that there are significant differences in learning motivation before and after using visual learning media.